Optimalisasi Perpustakaan Desa Berbasis Asset-Based Community Development: Strategi Pemberdayaan Literasi Di Plabuhanrejo, Lamongan - Muhamad Arif; Febrilia Furiandini; Suci Nur Laili Istiqomah; Eva Ruspita Yanti; Istiani Maulidiyah; Moch. Ramadlan Sofyan (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
Community empowerment related to literacy through village library management has the aim of supporting the literacy movement and community interest in reading in Plabuhanrejo village, Mantup District, Lamongan Regency. The method used in this research is the ABCD (asset-based community development) method; this method is an approach to community development. In the ABCD method, there are 5 procedures used, namely define, discover, dream, design, and deliver destiny. This community empowerment program can be implemented well and optimally. The results of the research show that books used as village libraries have a positive influence in overcoming various problems faced by the village, where initially the culture of literacy in the community began to decline, increasing day by day.